2020
DOI: 10.3390/f11020156
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Reveals the Mechanism of Picea crassifolia Survival for Alpine Treeline Condition

Abstract: The physiological mechanisms driving treeline formation succession captured the attention of ecologists many years ago, yet they are still not fully understood. In this study, physiological parameters (soluble sugars, starch, and nitrogen) were investigated in combination with transcriptomic analysis in the treeline tree species Picea crassifolia. The study was conducted in the middle of Qilian Mountain Reserves, Gansu Province, China, within the elevation range of 2500–3300 m. The results showed that the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Total RNAs were isolated from 3 kinds of tissues (leaves, phloem, and xylem from the current-year branches) using a Sangon Total RNA Purification Kit according the manufacturer’s protocol (Shanghai Sangon, Shanghai, China). The libraries were constructed and sequenced with the Illumina HiSeq 2500 platform (Illumina, San Diego, CA, USA), as described in our previous report [ 25 ]. An index of the reference genome was built using Bowtie v2.0.6, and single-end clean reads were aligned with the reference genome using TopHat v2.0.9 [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNAs were isolated from 3 kinds of tissues (leaves, phloem, and xylem from the current-year branches) using a Sangon Total RNA Purification Kit according the manufacturer’s protocol (Shanghai Sangon, Shanghai, China). The libraries were constructed and sequenced with the Illumina HiSeq 2500 platform (Illumina, San Diego, CA, USA), as described in our previous report [ 25 ]. An index of the reference genome was built using Bowtie v2.0.6, and single-end clean reads were aligned with the reference genome using TopHat v2.0.9 [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…A study of two-year drought stress on eleven tree species (six gymnosperm and five angiosperm species) demonstrated that the drought-resistant species had higher contents of flavonoids and polyphenols accompanied by higher leaf mass per area and higher photosynthetic rate [ 24 ]. In addition, many genes involved in flavonoid biosynthesis were found to be upregulated, while most photosynthesis-related genes were downregulated, in Picea crassifolia at a higher elevation compared to a lower one [ 25 ]. These results have demonstrated that polyphenols may play key roles in the survival of trees under various stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…and also explored the causes of growth cessation in Qinghai spruce under the climate change [31]. However, no combined BAI was available to study the factors limiting the growth of Qinghai spruce at different elevations [32,33]. In this paper, we have calculated the BAI of Qinghai spruce using the original tree ring width chronology method and compared the patterns of change in NSC and its components' concentrations between the elevations and tissues available in the Qilian Mountains.…”
Section: Introductionmentioning
confidence: 99%